Gene specific therapies: the next therapeutic milestone in neurology - Brenner, David; Ludolph, Albert C.; Weishaupt, Jochen H. (Neurological research and practice, 2020)
Gene selective approaches that either correct a disease mutation or a pathogenic mechanism will fundamentally change the treatment of neurological disorders. Basically, gene specific therapies are designed to manipulate RNA expression or reconstitute gene expression and function depending on the disease mechanism. Considerable methodological advances in the last years have made successful clinical translation of gene selective approaches possible, based on RNA interference or viral gene reconstitution in spinal muscular atrophy (SMA), Duchenne muscular dystrophy (DMD), and familial amyloid polyneuropathy (FAP). In this review, we provide an overview of the existing and coming gene specific therapies in neurology and discuss benefits, risks and challenges.